Menjembatani budaya dan logika: eksplorasi geometri tanjak unak serantau melalui geogebra sebagai solusi numerasi di era kurikulum merdeka - Nasrullah, Amri; Almaida; Dependri; Rahman, Muhamad Amar; Hasanah, Uswatun; Afri, Lusi Eka (Universitas Muhammadiyah Prof. DR. HAMKA, 2024)
Purpose: This research addresses the persistent challenge of low student numeracy by developing ethnomathematics-based interactive media focused on the cultural artifact of Tanjak Unak Serantau for geometry instruction.Design/methodology/approach: Following the 4-D development framework—comprising define, design, develop, and disseminate stages—this study engaged junior high school students and expert validators. The research utilized validation instruments, practicality surveys, and numeracy assessments to evaluate the GeoGebra-assisted prototype.Findings: The developed media achieved a high category of validity from experts in mathematics education and informatics. Empirical results demonstrated that the tool is highly practical and effective, as evidenced by the significant attainment of classroom mastery standards across sequential cycles.Practical implications: This innovation provides educators with a dynamic pedagogical tool that bridges abstract geometric theorems with tangible cultural symbols, fostering a more engaging and meaningful learning environment.Originality/value: The study contributes to the literature by digitizing local Malay wisdom into a dynamic geometry environment, offering a unique synthesis of traditional heritage and modern educational technology. Purpose: Penelitian ini menjawab tantangan rendahnya numerasi siswa melalui pengembangan media interaktif berbasis etnomatematika pada artefak budaya Tanjak Unak Serantau untuk pembelajaran geometri.Design/methodology/approach: Mengacu pada kerangka pengembangan 4-D—meliputi tahap pendefinisian, perancangan, pengembangan, dan penyebaran—studi ini melibatkan siswa sekolah menengah pertama serta para pakar validator. Instrumen penelitian mencakup lembar validasi, survei kepraktisan, dan asesmen numerasi untuk mengevaluasi purwarupa berbantuan GeoGebra.Findings: Media yang dikembangkan mencapai kategori validitas yang sangat tinggi dari para ahli pendidikan matematika dan informatika. Hasil empiris menunjukkan bahwa media ini sangat praktis dan efektif, terbukti dari pencapaian standar ketuntasan klasikal yang signifikan pada siklus yang berurutan.Practical implications: Inovasi ini menyediakan sarana pedagogis dinamis bagi pendidik untuk menjembatani teorema geometri abstrak dengan simbol budaya nyata, sehingga menciptakan lingkungan belajar yang lebih menarik dan bermakna.Originality/value: Studi ini berkontribusi pada literatur melalui digitalisasi kearifan lokal Melayu ke dalam lingkungan geometri dinamis, menawarkan sintesis unik antara warisan tradisional dan teknologi pendidikan modern.